Characterization of water in diesel emulsion - Karim, Z.A.A. (EDP Sciences, 2014)
Water in diesel emulsion, as an option fuel, has potential to simultaneously reduce the formation of both nitrogen oxides and particulate matters in diesel engine. However, the capability of this fuel strongly dependent on the type of emulsion, stability of the emulsified fuel and the physio-chemical properties. In this study, water in diesel emulsion fuels of 5, 10, 20, water by volume was prepared by a mechanical homogenizer. Physical and chemical properties of the emulsion were examined as these properties could influence the spray characteristics of the emulsions which significantly affect the ignition delay and flame propagation. Density and viscosity was found to be higher for all of the water in diesel emulsion than pure diesel at all measured temperatures whereas the carbon contents for water in diesel emulsion with 10 and 20 water were low. Droplet size of the emulsion was found to be less than 2Î¼m. The actual water content in the emulsified fuel was found to be lesser than the mixed amount. Â© 2014 Owned by the authors, published by EDP Sciences.